Penggunaan Papan Magnet untuk Meningkatkan Hasil Belajar Siswa pada Materi Volumedi Sekolah Dasar - Prastiyo, Fendika (Jurnal Didaktika Pendidikan Dasar, 2025)
The magnet ic board is a modified teaching aid to clarify the concept of converting volume units from km3 to liters or vice versa. The purpose of using magnet ic board Media is to improve student learning outcomes in volume material in grade VI of SDN Sepanjang 2. The use of media in learning uses Classroom Action Research (CAR) with 2 cycles. The learning outcomes of grade VI students in each cycle are: Pre-cycle, 1 child completed (3%), 28 children did not complete (97%). Cycle-1, 8 children completed (28%), 21 children did not complete (72%). Cycle-2, 21 children completed (72%), while 8 children did not complete (28%). It can be concluded that the use of magnet ic board media can improve participant learning outcomes in volume material. The results of the teacher response questionnaire in the use of magnet ic board Media showed that 80% were very good for use in the learning process and could be used with slight revisions (practicality value).